2014
DOI: 10.1371/journal.pone.0088538
|View full text |Cite|
|
Sign up to set email alerts
|

CMV Latent Infection Improves CD8+ T Response to SEB Due to Expansion of Polyfunctional CD57+ Cells in Young Individuals

Abstract: Cytomegalovirus (CMV) latent infection has a deleterious effect on the efficacy of influenza vaccination in the elderly, suggesting that CMV restricts immunological diversity impairing the immune system functionality in old age. Polyfunctional T cells produce multiple cytokines and higher amounts than mono-functional T cells. High number of polyfunctional T cells correlates with better prognosis during infection. Thus, the efficiency of T cell response associates with quality (polyfunctionality) rather than wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 44 publications
(59 reference statements)
8
61
0
1
Order By: Relevance
“…The effects of CMV infection on host immunity are not always deleterious, and CMV might have a beneficial effect on the immune system by providing immune protection against other pathogens (so-called heterologous immunity [40]) in younger healthy people. This could explain why humans (and many other species) tolerate the very high prevalence of this infection, and it is consistent with the notion of antagonistic pleiotropy [41][42][43]. Certain biological features can be selected as favorable during youth but become harmful with age (ie, during a stage of life that is neutral in terms of evolutionary selection) [44].…”
Section: And the Host Immune Systemsupporting
confidence: 72%
“…The effects of CMV infection on host immunity are not always deleterious, and CMV might have a beneficial effect on the immune system by providing immune protection against other pathogens (so-called heterologous immunity [40]) in younger healthy people. This could explain why humans (and many other species) tolerate the very high prevalence of this infection, and it is consistent with the notion of antagonistic pleiotropy [41][42][43]. Certain biological features can be selected as favorable during youth but become harmful with age (ie, during a stage of life that is neutral in terms of evolutionary selection) [44].…”
Section: And the Host Immune Systemsupporting
confidence: 72%
“…CMV seropositivity has also been shown to induce the expansion of polyfunctional CD8+ T cells (CD8+CD57+) secreting multiple cytokines (IFN-γ, TNF-α), which can degranulate in response to stimulation, and are therefore crucial for the generation of optimal responses to infections and vaccines (Pera et al 2014). The authors of this study have suggested that CMV seropositivity may provide protection against some pathogens by keeping the immune system in a state of alert.…”
Section: CMV Infectious Diseases and Vaccine Responsesmentioning
confidence: 90%
“…In the elderly, chronic latent HCMV infection increases the mortality rate, which could be attributed to HCMV-induced immunosenescence with decreased immunity to microbes and cancers (Pawelec et al, 2010;Sansoni et al, 2014;Savva et al, 2013). In the non-elderly, on the other hand, chronic HCMV infection may actually be beneficial in that it augments the T-cell immunity and has been associated with a reduced cancer risk in transplant patients (Couzi et al, 2010;Furman et al, 2015;Pera et al, 2014). In this study, significant intra-tumoural inflammatory responses were more frequently observed in HCMVpositive tumours, suggesting that viral replication may activate the immune response in the tumour microenvironment and contribute to a favourable prognosis (Naito et al, 1998).…”
Section: Discussionmentioning
confidence: 99%